Erupting mandibular second molar concomitant with complex odontome and supernumerary tooth in a 13-year-old boy: A case report - Krishnan, M Amrutha; Vidhya Vijayan, M C; Sreejith, V P; Puthalath, Ushas; Jose Tom, Jibin (Indian Journal of Case Reports, 2024)
Odontomas are the most frequent hamartomatous developmental abnormality. The condition frequently correlates with one or more unerupted teeth and is often detected through the failure of teeth to erupt at the expected time. Although most cases were discovered that were impacted within the jaw, there are scenarios where odontomas have erupted into the oral cavity. The majority of odontomas are asymptomatic; however, these anomalies can cause delayed eruption, impaction, or even result in the retention of primary teeth. Odontomas are atypical calcified aggregations of dental tissues such as enamel, dentin, pulp, and cementum and originate from odontogenic epithelium thereby, classifying them as mixed odontogenic tumors. Literature suggests that their etiology can be local trauma, infection, or genetic mutations, yet the precise cause remains unknown. This case report presents a complex odontome and a supernumerary tooth associated with a partially erupted second molar in a 13-year-old patient with radiological manifestations and surgical management.